The Factors in Influencing the Use of an E-Hailing Services Among University Students - Hazimi, Anis Humaira; Ahmad Termida, Nursitihazlin (Recent Trends in Civil Engineering and Built Environment, 2023)
The demand for online services is increasing day by day. In addition, as the Covid-19 outbreak started, people tend to use online food delivery (OFD) due to many restrictions and the new norm. Hence, this issue needs to be analysed so that the service can be improved especially during this critical condition. For this research, the scope of the study is focused on Universiti Tun Hussein Onn Malaysia (UTHM) undergraduate students. This study aims to determine the use of OFD among UTHM students. In order to collect the data, Google Form online survey has been distributed and 200 respondents have participated in the data collection stage. Mean score analysis has been applied to analyse the data gathered by using Statistical Package for the Social Science (SPSS) software version 26. However, the study found that UTHM students rarely use OFD hence the answer collected is based more on perception rather than firsthand experience. Thus, this paper has proposed some initiatives that can be applied to increase the usage of OFD among students such as reevaluating the price set by the vendors and collaborating with the government to provide subsidies of OFD especially to the students from B40 families.